All-Inside Anterior Cruciate Ligament Tibial Avulsion Repair - Jagtap, Satyajeet (Arthrosc Tech, 2021)
Anterior cruciate ligament (ACL) tibial avulsion occurs predominantly in children and young adults. It is seen in association with injuries due to hyperextension usually involving movements that are similar to riding a bicycle. Bony ACL avulsion is associated with severe restriction of knee range of motion, swelling, inability to bear weight, and continuous pain. Acute swelling does not allow a conclusive clinical examination. Bony ACL avulsion from the tibial side has been treated by various methods ranging from conservative management to a wide range of operative procedures. The various operative procedures that have been described require challenging operative skills, time, and resources, making these techniques demanding and technically challenging. We describe a technique for the treatment of Meyers-McKeever type II, III, and IV bony tibial ACL avulsions that uses regular anterolateral and anteromedial portals with an additional transpatellar portal. The avulsed fragments along with the ACL are held and buttressed with the help of FiberWires and fixed with the intra-articular portion of the proximal tibia. The technique is performed in an all-inside manner and is easy to master, even for beginners.